Political Sociology - Berberoglu, Berch (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The role of the state, and politics in general, as well as the social basis of power and political phenomena, constitute the central, defining features of the sub-field of political sociology, which informs our understanding of the major political institutions that dominate society and social life. This course will provide a systematic overview of political sociology: we will examine the origins and development of the state, the nature and sources of power in contemporary society, the relationship between class and state, the politics of various classes, the politics of race and gender, the mechanisms of political control and domination, political organization, the politics of social movements, the nature and dynamics ofnationalism and ethnic conflict, and a host of other topics related to politics and society. Political sociology addresses many of these issues and places them within a comparative, historical, and sociological perspective.